Edukasi dan Strategi Terapi Latihan Berbasis Rumah untuk Knee Osteoarthritis pada Lansia di Posyandu Lansia RW 3 Tulusrejo Kota Malang - Raray Inas Prianggalistiari; Sri Sunaringsih Ika Wardojo; Bonita Suharto (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Elderly is the final stage of adulthood where a person will enter the age of 60 and above. In the elderly, osteoarthritis occurs more often in the knee joints (knee osteoarthritis) than in other areas, such as the joints of the hands and hips. The most common clinical symptoms are pain that arises gradually and worsens over time, stiffness, crepitus, and joint motion restrictions. The purpose of this study was to educate the elderly about the meaning of knee osteoarthritis, risk factors, signs and symptoms, prevention efforts, and exercises that can be done at home. The method used was to provide counseling in the form of health promotion about knee osteoarthritis to the elderly with leaflets as a medium for counseling. Pre-test and post-test were given to measure the effectiveness of counseling. The conclusion of this study was that the activity went smoothly, was well realized, and received enthusiasm from the participants. The results obtained based on the evaluation were an increase in the knowledge and understanding of the elderly community in Tulusrejo Village regarding knee osteoarthritis.